The sacrament of anointing of the sick - Larson-Miller, Lizette (Collegeville, Minn. : Liturgical Press, 2005)
"Overviews, affirms, and critiques the current Roman Catholic rites for the pastoral care of the sick and engages them through contemporary theological, liturgical, pastoral, and cultural issues, focusing particularly on the sacramental heart of the rites, the anointing of the sick"--Provided by publisher.
An overview of the rites of pastoral care of the sick -- The threefold ritual center of anointing of the sick -- Theological questions from the rite -- The contexts of church and culture for pastoral care of the sick.
Includes bibliographical references and indexes.
Keywords: Catholic Church -- Doctrines; Church work with the sick -- Catholic Church; Unction